Molecular Prevalence and Identification of Ehrlichia canis and Anaplasma platys from Dogs in Nay Pyi Taw Area, Myanmar - Myint Myint Hmoon; Lat Lat Htun; May June Thu; Hla Myet Chel; Yu Nandi Thaw; Shwe Yee Win; Nyein Chan Soe; Yadanar Khaing; Su Su Thein; Saw Bawm (Veterinary Medicine International)
Ticks are vectors of different types of viruses, protozoans, and other microorganisms, which include Gram-negative prokaryotes of the genera Rickettsiales, Ehrlichia, Anaplasma, and Borrelia. Canine monocytic ehrlichiosis caused by Ehrlichia canis and canine cyclic thrombocytopenia caused by Anaplasma platys are of veterinary importance worldwide. In Myanmar, there is limited information concerning tick-borne pathogens, Ehrlichia and Anaplasma spp., as well as genetic characterization of these species. We performed nested PCR for the gltA gene of the genus Ehrlichia spp. and the 16S rRNA gene of the genus Anaplasma spp. with blood samples from 400 apparently healthy dogs in Nay Pyi Taw area. These amplicon sequences were compared with other sequences from GenBank. Among the 400 blood samples from dogs, 3 (0.75%) were positive for E. canis and 1 (0.25%) was positive for A. platys. The partial sequences of the E. canis gltA and A. platys 16SrRNA genes obtained were highly similar to E. canis and A. platys isolated from different other countries.